Lorentz Theory Revisited - Blanovsky, Anatoly (European Journal of Applied Sciences, 2023)
Long before quantum mechanics, Lorentz suggested that some disturbances, like waves, travel with particles through a certain medium -motionless ether. It is shown that these waves are described by the Klein-Gordon equation and dispersion relation w2=c2k2+wc2. In hydromechanics, they are known as non-propagating waves and a constant wc is called the cutoff frequency. A quantum object is considered as a vibrating particle or material body with a rest mass m moving in resonance with wave characterized by the cutoff or Compton frequency wc=mc2/ .